Efektivitas Latihan Abdominal Strecting dan Senam Disminorhea terhadap Penurunan Disminorhea - Mei Puji Lestari; Nofa Anggraini (Malahayati Nursing Journal, 2024)
ABSTRACT According to WHO data, it was found that the incidence of women experiencing menstrual pain was 1,769,425 people (90%) with 10% - 15% experiencing severe menstrual pain. To determine the effectiveness of abdominal stretching exercise and dysmenorrhea gymnastics on reducing primary dysmenorrhea. Using quasi-experimental with two group pretest-posttest design. The study population was young women at TPMB Joglo who had menstruated, namely 30 respondents. The research sample amounted to 30 respondents who were divided into two groups, namely 15 respondents of the abdominal streatching group and 15 respondents of dysmenorrhea gymnastics. bivariate analysis using the Wilcoxcone test. The results of the Wilcoxone Signed Test obtained a value of p=0.000 0.05 so it can be concluded that there is an effectiveness of abdominal stretching exercises on reducing dysminorrhea. While based on the results of the Wilcoxone range list test obtained a value of p = 0.001 0.005 so it can be concluded that there is an effectiveness of dysminorrhea gymnastics on the decline of dysminorrhea. In conclusion, abdominal stretching exercises and dysminorrhea exercises are effective for reducing menstrual pain in adolescent girls. Suggested in this study for educational institutions, for research sites, for respondents and for further researchers. Keywords: Exercise Abdominal Stretching, Menstrual Pain  ABSTRAK Menurut WHO didapatkan data bahwa angka kejadian perempuan yang mengalami nyeri menstruasi sejumlah 1.769.425 jiwa (90%) dengan 10% – 15% mengalami nyeri mestruasi berat. Untuk mengetahui efektivitas abdominal stretching exercise dan senam dismenorea terhadap penurunan dismenorea primer. Menggunakan quasi eksperimental dengan rancangan two group pretest-posttest design. Populasi penelitian adalah remaja putri di TPMB Joglo yang sudah menstruasi yaitu sebanyak 30 responden. Sampel penelitian berjumlah 30 responden yang dibagi menjadi dua kelompok yaitu 15 responden kelompok abdominal streatching dan 15responden senam disiminore. analis bivariat emenggunakan uji Wilcoxcone. Hasil uji Wilcoxone Signed Test diperoleh nilai nilai p=0.0000,05 sehingga dapat disimpulkan terdapat efektivitas Latihan abdominal stretching terhadap penurunan disminore. Sedangkan berdasarkan hasil uji wilcoxone range list di peroleh nilai p = 0,0010,005 sehingga dapat disimpulkan terdapat efektivitas senam disminore terhadap penurunan disminore. Simpulan di dapatkan Latihan abdominal stretching dan senam disminore efektif untuk penurunan nyeri haid pada remaja putri. Disaran dalam penelitian ini untuk Institusi pendidikan, untuk tempat penelitian, untuk responden dan untuk peneliti selanjutnya. Kata Kunci: Latihan Abdominal Stretching, Disminore, Senam Disminore